Effects of Soluble Silicate and Nanosilica Application on Rice Nutrition in an Oxisol - FÉLIX ALVAREZ, Rita de Cassia; PRADO, Renato de Mello [UNESP]; FELISBERTO, Guilherme [UNESP]; FERNANDES DEUS, Angélica Cristina [UNESP]; LIMA DE OLIVEIRA, Raimundo Leonardo [UNESP] (Elsevier, 2018)
Silicon (Si) has been supplied to plants via application of calcium silicate to soil; however, high doses of calcium silicate are required because of its low solubility. Nanoparticles can reduce Si doses and be applied to seeding furrows. This study investigated the effects of liquid Si sources, i.e., highly soluble silicate (115.2 g L−1 Si and 60.5 g L−1 Na2O) and nanosilica (< 200 nm), on Si uptake by rice plants, plant lignification, plant C:N:P stoichiometry, plant physiology, and grain yield using an Oxisol under greanhouse condistions. The treatments included the application of nanosilica and soluble silicate to seeding furrows at Si doses of 0, 605, 1210, and 2 420 g ha−1. Plant uptake and treatment effects were evaluated by measuring C and lignin contents, Si, N, and P accumulation, physiological characteristics, and grain yield of rice. The deposition of silica bodies and amorphous silica in the flag leaves was analyzed using scanning electron microscopy. Application of liquid Si increased Si accumulation in rice by 47.3% in relation to the control (0 g ha−1 Si), regardless of the Si sources used. Nanosilica application increased leaf lignin content by 112.7% when compared to that in the control. Silicon moderately affected the net C assimilation (increased by 1.83%) and transpiration rates (increased by 48.3%); however, Si influenced neither plant growth nor grain yield of rice. These results are explained by the lack of biotic or abiotic stress in rice plants during the experiment. To the best of our knowledge, in Brazilian agriculture, this is the first report on the use of nanosilica as a Si fertilizer and its effect on plant nutrition. This study provides evidence that rice plants absorb and accumulate nanoparticles; however, further studies are required to investigate the use of nanoparticles in other plant species.
Keywords: C:N:P stoichiometry; grain yield; leaf lignin; net C assimilation; plant physiology; silicon source